Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3844/ajnsp.2011.112.121
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Geometry of Silver Nanoparticles Synthesis in <i>Chrysosporium Tropicum</i> and <i>Fusarium Oxysporum</i>

Abstract: Problem statement: Biosynthesis of nanoparticles using fungal cells is a novel approach to develop biotechnological possess such as bioleaching and bioremediation. In the present study, an effort was made to investigate the effect of physio-chemical parameters on the silver nanoparticle formation with the fungus Chrysosporium tropicum Carmichael and Fusarium oxysporum Schltdl. Approach: The possibilities to manipulating the geometry of silver nanoparticles by altering the key growth parameters such as pH, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
(19 reference statements)
3
7
0
Order By: Relevance
“…Birla et al (25) showed the formation of larger particles at acidic PH due to aggregation, while at alkaline (pH 9 and pH 11) monodispersed and stable SNPs were found. Our results correlate with Xue et al (17) who reported that the alkaline pH was more favorable for production of SNPs by the fungus Arthroderma fulvum and disagreement with Soni& Prakash (27) who reported increase in absorption with decrease in pH. The availability of OH-ions in alkaline medium is very important for reduction of metal ions.…”
Section: Discussionsupporting
confidence: 75%
“…Birla et al (25) showed the formation of larger particles at acidic PH due to aggregation, while at alkaline (pH 9 and pH 11) monodispersed and stable SNPs were found. Our results correlate with Xue et al (17) who reported that the alkaline pH was more favorable for production of SNPs by the fungus Arthroderma fulvum and disagreement with Soni& Prakash (27) who reported increase in absorption with decrease in pH. The availability of OH-ions in alkaline medium is very important for reduction of metal ions.…”
Section: Discussionsupporting
confidence: 75%
“…lycopersici; however, XRD pattern showed also the presence of AgCl nanoparticles. Soni and Prakash (2011) demonstrated the presence of Ag o nanoparticles together with silver oxides mixtures and other impurities from F. oxysporum Schltdl 2480 and from Chrysosporium tropicum Carmichael-2828 strains. Penicillium atramentosum KM was suggested to be able to produce Ag o nanoparticles; however, the XRD pattern represented a mixture of silver oxide nanoparticles and not Ag o nanoparticles (Sarsar et al 2015).…”
Section: Fungimentioning
confidence: 96%
“…This is due to the influence of variations in pH on the generation of nucleation centers, which are crucial for the development of these materials. While synthesizing NPs, the manipulation of pH levels can be employed as a means to regulate both the size and geometry of the particles, as observed in case of silver NPs generated from algal species [164]. It has been observed in multiple investigations that the size of NPs is anticipated to be greater in acidic fluids compared to basic media for selected nanomaterials.…”
Section: Effect Of Ph On Np Synthesismentioning
confidence: 99%